Lecture Note
University
California State UniversityCourse
MATH 150B | Calculus IIPages
1
Academic year
2023
Andrew Mathis
Views
0
p {margin: 0; padding: 0;} No Date . 6 FUNCTION OF A FUNCTION ("BRACKET" Rule) y (ECX) y nxf'(x) x Flx) n-1 Liff middle e.g g (2x3) + 3x y'= Cx (6x' 3) (2x3 +3x) one less Rerwite inside for power power to the front of bracket WARNING !! The cambridge book uses the chin rule to do this cambridge working below g (2x3+3x) y=46 u = (2x'+3x) dy 645 du = (6x2 + 3) du dx Using "chain " rule dy = ty x du dx du dx dy = but * (6x'+3) dx = 6 (6x2+3) (2x'+3x)5
Bracket Rule
Please or to post comments